Assessing Sustainability of Small Scale Business Opportunities in Nigeria: Prospect and Challenges - Agunbiade, Asimiyu Kola; Afolabi, Olasunkanmi Muftau; Olaiya, Abiodun Lukuman; Omotayo, Gbenga Oluyemi (NIU Journal of Humanities, 2020)
Small  Scale  Enterprises  have  been  accepted  worldwide  as  instrument of economic  growth  and development. No wonder  that government, particularly in the developing countries  has made tremendous efforts and  establish  policies to  enhance  the  capacity  of small  scale  enterprises.  However, despite government institutional and policies support to enhancing the capacity of small scale enterprises, small scale enterprises has fallen  short  of  expectations. This then, generated serious concern and skepticism on whether it can bring about economic growth and national developments in Nigeria. This type of business are faced  with  significant  challenges  that  compromise  their  ability  to  function  and  to  contribute  optimally  to  the economy. Hence there is need to examine the challenges and prospects of small scale enterprises opportunities in Nigeria.Survey in the form of descriptive research design were used, 152 questionnaires were administered to the staff of selected poultry farm in kwara state out of which 15 were wrongly fill nor returned the remaining 137 were used for the analysis.   Proportional sampling method was used to determine the sample size. Data generated through questionnaire were analysed using both regression and Pearson correlation. Data were analysis, at (R) 0.05 level of significance and the result revealed that access to finance and capital have significant impact on SMEs Drives.(b=0.741, t=3.842, df=4 p(.000)<0.05).This study was conducted in kwara state, Nigeria. The phenomenal growth of small enterprise in Nigeria is mainly due to the peopleâ€™s quest to be self-employed and not because it is easy to establish or manage. Financial  constraints  and  Lack  of  management  skill  hamper  the efficient  performance  of  small scale enterprises in  Nigeria.  In  view  of  this,  we  recommend  that government  and  other  non-governmental  organization  should  regularly  organize  seminars  for  potential  and actual small and medium enterprise operators on how to plan, organize, direct and control their businesses, and that small business  enterprises  operatorsâ€™  should  device  effective  marketing  strategies  and  good management customers relations at all times. Keywords: Small Business Enterprises, Opportunities, Challenges, Prospect, Development